Cis-4-[18F]fluoro-D-proline detects neurodegeneration in patients with akinetic-rigid parkinsonism. Issue 4 (April 2019) - Sommerauer, Michael; Galldiks, Norbert; Barbe, Michael T.; Stoffels, Gabriele; Willuweit, Antje; Coenen, Heinz H.; Schroeter, Michael; Timmermann, Lars; Fink, Gereon R.; Langen, Karl-Josef
Abstract : Objectives: This study aimed to investigate whether the amino acid PET tracer cis -4-[ 18 F]fluoro-D-proline [D- cis -[ 18 F]FPro] shows increased uptake in the basal ganglia of patients with neurodegenerative akinetic-rigid parkinsonism. D- Cis -[ 18 F]FPro is a sensitive PET tracer for inflammation-associated neurodegeneration in animal models. We hypothesized that D- cis -[ 18 F]FPro might also be a sensitive marker of alterations of the basal ganglia in parkinsonian syndromes. Participants and methods: Ten patients with neurodegenerative akinetic-rigid parkinsonism (five with idiopathic Parkinson's disease and five with atypical parkinsonian syndromes) were imaged with D- cis -[ 18 F]FPro and compared with 13 patients with brain tumors who had no basal ganglia involvement. PET images 20–50 min after injection were evaluated and tracer uptake in the basal ganglia was quantified using volume-of-interest analysis with basal ganglia to background ratios. The severity of disease was assessed with unified Parkinson's disease rating scale III and correlated with D- cis -[ 18 F]FPro uptake. Results: In patients with parkinsonism, volume-of-interest analysis showed mild, but significantly increased D- cis -[ 18 F]FPro uptake in the basal ganglia, pronounced in the lenticular nucleus. Disease severity correlated with D- cis -[ 18 F]FPro uptake in the right pallidum ( r =−0.687, P =0.041). Conclusion: Data suggest that D- cis -[ 18 F]FPro is a sensitive marker of inflammation-associated degenerative processes in parkinsonian syndromes. Abstract : Supplemental Digital Content is available in the text.